Comparative analysis of company's financial performance before and after tax amnesty; evidence from Indonesia - Ratno Agriyanto; Della Aprilia (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2020)
Purpose – The purpose of this study is to analyze differences in financial performance before and after the tax amnesty was applied until the third period.Method – This research uses a comparative method with a quantitative approach. The data collection technique used the documentation method. The research data were in the form of annual reports and financial reports of issuers of the Indonesia Stock Exchange. The results showed the financial performance before and after the tax amnesty up to the third period in the property and real estate sub-sector companies.Result – The result shows a significant difference between before and after the tax amnesty until the third period. However, there is no significant difference between Debt to Equity Ratio and Return on Equity before and after the tax amnesty until the third period. The analysis results up to the third period regarding company value shows that there are differences in company value before and after the tax amnesty up to the third period.Implication – The study offers alternative perspective about tax amnesty. Most of the time companies are reluctant to engage with tax payment.By applying tax amnesty, both ruling government and companies are both be benefited. Originality – This study is among few studies about the impact of tax amnesty on financial performance in Indonesia.